Has the quality of health care for the immigrant population changed during the economic crisis in Catalonia (Spain)? Opinions of health professionals and immigrant users - Victoria Porthé; Ingrid Vargas; Elena Ronda; Davide Malmusi; Lola Bosch; M. Luisa Vázquez (Elsevier, 2018)
Objective: To analyse changes in health professionals' and immigrant users' perceptions of the quality of care provided to the immigrant population during the crisis. Methods: A qualitative descriptive-interpretative and exploratory study was conducted in two areas of Catalonia. Semi-structured individual interviews were used with a theoretical sample of medical (n = 24) and administrative (n = 10) professionals in primary care (PC) and secondary care (SC), and immigrant users (n = 20). Thematic analysis was conducted and the results were triangulated. Results: Problems related to technical and interpersonal quality emerged from the discourse of both professionals and immigrants. These problems were attributed to cutbacks during the economic crisis. Regarding technical quality, respondents reported an increase in erroneous or non-specific diagnoses, inappropriate use of diagnostic tests and non-specific treatments, due to reduction in consultation times as a result of cuts in human resources. With regard to interpersonal quality, professionals reported less empathy, and users also reported worse communication, due to changes in professionals' working conditions and users' attitudes. Finally, a reduction in the resolution capacity of the health services emerged: professionals described unnecessary repeated PC visits and limited responses in SC, while young immigrants reported an insufficient response to their health problems. Conclusion: The results indicate a deterioration in perceived technical and interpersonal quality during the economic crisis, due to cutbacks mainly in human resources. These changes affect the whole population, but especially immigrants. Resumen: Objetivo: Analizar los cambios en la calidad percibida de la atención a la población inmigrante durante la crisis económica, desde la perspectiva de profesionales e inmigrantes. Métodos: Estudio cualitativo descriptivo-interpretativo y exploratorio en dos áreas de Cataluña, mediante entrevistas individuales semiestructuradas a una muestra teórica de médico/as (n = 24) y administrativas (n = 10) de atención primaria (AP) y secundaria (AS), e inmigrantes (n = 20). Se realizó un análisis temático de contenido y se triangularon los resultados. Resultados: Del discurso de profesionales e inmigrantes emergen problemas en la calidad técnica e interpersonal, que relacionan con la reducción de recursos durante la crisis. Respecto a la calidad técnica, los/las informantes describen un aumento de diagnósticos erróneos o inespecíficos, un uso inadecuado de pruebas y tratamientos inespecíficos, debido a la disminución del tiempo de consulta por la reducción de recursos humanos. Respecto a la calidad interpersonal, los/las profesionales señalaron menor empatía, mientras que los/las inmigrantes, además, una peor comunicación, que atribuyeron al cambio en las condiciones laborales de los/las profesionales y en la actitud de los/las inmigrantes. Finalmente, emergió la disminución de la capacidad resolutiva de los servicios: según los/las profesionales, por la repetición de consultas innecesarias en AP y limitadas en AS; según los/las inmigrantes jóvenes, por respuestas limitadas a sus problemas de salud. Conclusiones: Los resultados apuntan a un empeoramiento de la calidad técnica e interpersonal durante la crisis, por reducción de recursos, principalmente humanos, que afectan al conjunto de la población, pero en especial a las personas inmigrantes. Keywords: Migrants, Health services, Quality of health care, Economic crisis, Health policy, Palabras clave: Inmigrantes, Servicios sanitarios, Calidad de la atención, Crisis económica, Políticas sanitarias